QoT AWARE LOAD BALANCING ROUTING IN MANET USING RELAY TYPE OF AMPLIFY AND FORWARD BASED COOPERATIVE COMMUNICATIONS - Binh, Le Huu; Tu, Vo Thanh; Tam, Nguyen Van (Journal of Computer Science and Cybernetics, 2020)
In research topics to improve the performance of the mobile ad hoc networks (MANET), the load balancing routing has been attracted many research groups because it is an effective solution to reduce the traffic congestion. However, for the mesh topologies as MANET, the load balancing routing can decrease the Quality of Transmission (QoT) because some routes can pass through many intermediate nodes, especially in the case of MANET using the relay type of amplify and forward (AF) based cooperative communications, where the power of the noise signal can be amplified at intermediate nodes. In this paper, we focus on investigating the QoT in MANET using AF. Thence, a load balancing routing algorithm that takes account of the QoT is proposed in order to improve the network performance. Our evaluation by simulation method has showed that the proposed algorithm can improve the network performance in terms of the QoT, blocking probability of data packet, and network throughput compared with the original routing algorithms